STRATEGIES IN APOLOGIZING AMONG WRITERS IN PEMBACA MENULIS COLUMN AT JAWA POS NEWSPAPER - PRATAMA, ALFIAN FEBRIANDI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Pratama, Alfian Febriandi. 2014. Strategies in Apologizing among Writers inPembaca Menulis Column at Jawa Pos Newspaper. Study Program of English,Department of Languages and Literature, Faculty of Cultural Studies, UniversitasBrawijaya, Malang. Supervisor: Nurul Chojimah. Co-Supervisor: Yana ShantiManipuspika.Key words: speech acts, apology strategies, Pembaca Menulis columnCommunication is a primary need of social life. Communication is also usedfor asking for an apology. Apology is a speech act used to restore relationshipsbetween a speaker (S) and a hearer (H) after S has offended H intentionally orunintentionally. Apology also happens in mass media. The researcher conducted aresearch about strategy in apologizing among writers in Pembaca Menulis column atJawa Pos newspaper published from 11thJanuary to 28thFebruary 2013. There aretwo problems to be solved: (1) what apology strategies are used among writers inPembaca Menulis column at Jawa Pos newspaper, and (2) How those strategies arelexically realized in direct and indirect speech acts.This research used qualitative approach because the analysis is in the form ofdescription rather than number. Then, the research was conducted throughdocumentary analysis because the researcher analyzed the writers’ utterance inPembaca Menulis column in Jawa Pos containing apology.The result of the research shows that there are seven types of apologystrategies found to enrich Trosborg’s theory, namely (1) confession, (2) explicitapology, (3) explicit apology followed by explanation, (4) indirect apology followedby explanation, (5) explicit apology followed by justification, (6) explicit apologyfollowed by admonition, and (7) rejection to apologize. The research also shows thatthere are 17 utterances using direct speech acts.Based on the findings, it is concluded that in Bahasa Indonesia, to apologizeis easy. The writers in Pembaca Menulis column apologize for some reasons. First,they realized their mistake; second, they prevented the complainer to make anothercomplaint, and third, the value of apology in Indonesia is lower than that in English-speaking country. Every language has it strategy to apologizing but the way toexpress the apology is influenced by the culture where the language is used. Theresearcher wants to suggest the next researchers who are interested in the same fieldto use objects which is collect by observing the natural conversation in BahasaIndonesia to enrich Trosborg’s theory.